Calcium chloride and ultraviolet radiation in tomato postharvest conservation (Research, Society and Development, 2021)
Tomato (Lycopersicon esculentum) is a climacteric product with a short post-harvest shelf life. The exogenous use of calcium chloride (CaCl2) and ultraviolet radiation (UV) has been shown to be efficient in maintaining the firmness and quality of several fruits. Therefore, this study aimed to evaluate the effects of exogenous application of calcium chloride and ultraviolet radiation on postharvest conservation of tomato fruits. For this, the fruits were: submerged in 1% calcium chloride and exposed to ultraviolet radiation; immersed in 1% calcium chloride only; and fruits exposed only to ultraviolet radiation. Fruits not submerged in CaCl2 and not exposed to UV radiation were used as controls. After application of treatments, fruits were stored under ambient conditions and evaluated at times 0, 3, 6, 9, 12 and 15 days after harvest. Fresh mass loss, fruit firmness, skin color, soluble solids content, pH, total titratable acidity, ratio between total soluble solids (TSS) and titratable acidity (ATT) were evaluated. There was an increase in fresh mass loss over time in all treatments. Fruits not immersed or those immersed in CaCl2+UV chloride showed greater firmness maintenance. It can be concluded that the fruits subjected to ultraviolet radiation showed less loss of fresh mass at the end of the analysis, and the use of calcium chloride together with UV radiation maintained the firmness of the fruits throughout storage.